Usage of vaccines and therapeutics in public health emergencies 1 - Kobinger, Gary (Henry Stewart Talks, 2020)
The burden of infectious diseases, Controlling infection disease and the effect on economy, The phylogenetic tree of Mononegavirales that includes Ebola virus, Outbreak of infectious diseases worldwide, Outbreak responses and tools that can be deployed to better control outbreak, Ebola virus outbreaks, Importance of developing novel vaccines and vaccine development process, Treating “first-responders” with vaccine against Ebola